2016
DOI: 10.1088/1742-6596/765/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Piezoelectric properties of half-Heusler compounds: A first principles study

Abstract: Abstract.We have investigated the semiconducting and piezoelectric properties of bulk MNiSn (M=Ti, Zr, Hf) type a half-Heusler compound with cubic F-43m symmetry by means of density functional theory (DFT). For electron exchange correlation a generalized gradient approximation (GGA) was used. Special attention was paid to establish a most favourble ground state configuration on magnetic as well as non-magnetic ordering. With fully optimized structure the electronic and ferroelectric calculation was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The Half Heusler alloys don't cease to demonstrate their great interest in technology since the discovery of half Heusler compounds by German engineer Heusler in 1903 [1]. The domains most used of these materials: are magnetism [2], piezoelectricity [3], and spintronics [4], and they are also intriguing prospects for ecologically friendly and low-cost thermoelectric materials [5]. In recent years, numerous studies of thermoelectrical materials have revealed their great potential for thermal heat conversion into electrical energy [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Half Heusler alloys don't cease to demonstrate their great interest in technology since the discovery of half Heusler compounds by German engineer Heusler in 1903 [1]. The domains most used of these materials: are magnetism [2], piezoelectricity [3], and spintronics [4], and they are also intriguing prospects for ecologically friendly and low-cost thermoelectric materials [5]. In recent years, numerous studies of thermoelectrical materials have revealed their great potential for thermal heat conversion into electrical energy [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one can refer to the studies on heterostructures based on binary semiconductors such as WSe 2 /GaN, 15 ZnS/ZnO, 16 and graphene-like III-nitride. 17 Extensive theoretical and experimental studies on Heusler alloys, especially half-Heuslers, have shown unique performances and properties such as piezoelectric, [18][19][20] optical behavior, 19,21,22 spintronic, [23][24][25] and topological insulation. [26][27][28] Various studies have also shown that the electronic junction of these alloys with semiconductors, insulators, or metals leads to improved properties or new features.…”
mentioning
confidence: 99%